Protein substrates of the arginine methyltransferase Hmt1 identified by proteome arrays. Issue 3 (February 2016) - Low, Jason K. K.; Im, Hogune; Erce, Melissa A.; Hart‐Smith, Gene; Snyder, Michael P.; Wilkins, Marc R.
Abstract : Arginine methylation on nonhistone proteins is associated with a number of cellular processes including RNA splicing, protein localization, and the formation of protein complexes. In this manuscript, Saccharomyces cerevisiae proteome arrays carrying 4228 proteins were used with an antimethylarginine antibody to first identify 88 putatively arginine‐methylated proteins. By treating the arrays with recombinant arginine methyltransferase Hmt1, 42 proteins were found to be possible substrates of this enzyme. Analysis of the putative arginine‐methylated proteins revealed that they were predominantly nuclear or nucleolar in localization, consistent with the localization of Hmt1. Many are involved in known methylarginine‐associated functions, such as RNA processing and ribonucleoprotein complex biogenesis, yet others are of newer classes, namely RNA/DNA helicases and tRNA‐associated proteins. Using ex vivo methylation and MS/MS, a set of 12 proteins (Brr1, Dia4, Hts1, Mpp10, Mrd1, Nug1, Prp43, Rpa43, Rrp43, Spp381, Utp4, and Npl3), including the RNA helicase Prp43 and tRNA ligases Dia4 and Hts1, were all validated as Hmt1 substrates. Interestingly, the majority of these also had human orthologs, or family members, that have been documented elsewhere to carry arginine methylation. These results confirm arginine methylation as a widespread modification and Hmt1 as the major arginine methyltransferase in the S. cerevisiae cell.